Efficiency of refractive lensectomy with multifocal iol implantation for hypermetropia and presbyopia correction - Zavgorodnyaya, N. G.; Bezdenezhnaya, O. A.; Yerohina, K. V.; Завгородня, Наталія Григорівна; Безденежна, Ольга Олександрівна (Запорізький державний медичний університет, 2018)
In connection with loss of natural accommodation after 40 years in patients with presbyopia and hypermetropia, a decrease in both near and far vision is observed. Increased patients' requirements for quality of vision and desire to achieve a spectacle independence for close and medium distances with the highest possible uncorrected long distance visual acuity often determine the choice of refractive lensectomy with the multifocal intraocular lens (IOL)implantation, which is an advanced technique of such refractive anomalies treatment. Objective. To evaluate the effectiveness of refractive lens replacement with the multifocal IOL implantation for hypermetropia and presbyopia correction. Materials and methods. A retrospective analysis of the refractive lensectomy with multifocal IOL implantation results (AT LISA 809M and AT LISA 839 MR TRI (Carl Zeiss, Germany) of 20 patients (34 eyes) with mild hyperopia (24 eyes) and moderate hyperopia (10 eyes) in combination with presbyopia was performed in the clinic "Visus" (Zaporozhye). The average age of the patients was 55,6±5,7 years, the number of men were 9 (45%), women – 11 (55%). The study inclusion criteria were: patients with hypermetropia and presbyopia, age > 40 years. Exclusion criteria were: preoperative corneal astigmatism measure > 0,75D, presence of concomitant ocular pathology, previous history of operation. All patients underwent a standard ophthalmological examination (visometry, autorefractometry, Maklakov tonometry, perimetry, biomicroscopy, ophthalmoscopy) before and 1 month after surgery. IOL calculations were performed using the IOL-Master 500 optical biometer (Carl Zeiss, Germany). Criteria for the surgical treatment effectiveness: achieving predicted visual acuity in the distance (equal to the corrected visual acuity before the operation), the absence of additional spectacle correction for near vision.
Keywords: тези доповідей